If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 14 = 4 Reorder the terms: 14 + y = 4 Solving 14 + y = 4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + y = 4 + -14 Combine like terms: 14 + -14 = 0 0 + y = 4 + -14 y = 4 + -14 Combine like terms: 4 + -14 = -10 y = -10 Simplifying y = -10
| (25)-(8)= | | 3(2-3y)+5y=3y | | -[11x-(3x+5)]=-6-[4(3x-4)-2x] | | 3(2x+1)=2(1+3x)-1 | | b-5=0 | | 2=(x-40) | | (19)-(15)= | | (10)-(-30)= | | .2(x+.2)=24 | | -0.5y-7=-7.5 | | (2x+17)+13= | | (32)-(-19)= | | 3900=58x | | 2(x+1)+3(x+2)= | | (23)-(-4)= | | a-13a=6 | | (47)-(33)= | | 21-5x=7-7x | | (.66x+18)=(2x-5) | | 21-5x=7+7x | | (12)-(42)= | | 21-5x=-7+7x | | 4q-15=16q-1 | | 6-x=3x | | 3x+12=-42+6x | | -6+7r=6+5r | | -7+7r=6+5r | | (-46)-(12)= | | (-x^2+5x-3)+(7x^2+4x+6)= | | 9+10x=-45+x | | 0.02*1.5= | | (49)-(32)= |